Moderating role of audit quality and firm size on pretax profit margin and related party transactions: evidence from Indonesia - Santosa, Perdana Wahyu; Rahayu, Sovi Ismawati; Simon, Zainal Zawir; Santoso, Pramesti Wulandari (Business: Theory and Practice, 2023)
This study examines the effect of related party transactions (RPTs) on pretax profit margin (PPM). It analyzes the moderating effect of audit quality and firm size based on a large panel of Indonesian-listed firms. The sample of three representative business groups from 2010–2021 and analysis uses the Generalized Method of Moments (GMM) estimator to control PPM as a proxy of taxable income. We document that this study finds that PPM(t-1) and RPT Sales negatively impact and are significant on firms’ PPM, consistent with the incentive alignment hypothesis. However, RPTs, RPT Loan, and RPT Receivables affect positively. We also find that audit quality strengthens the impact of RPT Loan and RPT Receivables on the PPM negatively and positively significantly; however weakens RPTs, RPT Sales, and RPT Expenses. Moreover, firm size weakens the effect RPTs on PPM. RPTs and tax avoidance are complex and multifaceted phenomena of corporate finance. Additional business groups and variables may have moderating and mediating effects on the impact of taxable income on the business group. Stakeholders, especially the government, should supervise and control RPTs activities comprehensively, especially on the types of RPT Sales and RPT Expenses transactions. The paper offers two contributions. First, it gathers the first evidence on the taxable income and RPTs practices and offers insights into Indonesia’s business group behavior. Second, the analysis examines eleven years considering the sensitivity of audit quality and firm size to RPTs and pretax profit margin.